Mechanical properties of PCL/PLA/PEG composite blended with different molecular weight (MW) of PEG for Fused Deposition Modelling (FDM) filament wire. - Abdul Haq, Reazul Haq; Marwah, Omar Mohd Faizan; Abdol Rahman, Mohd Nasroll; Ho, Fu Haw; Abdullah, Haslina; Ahmad, Said; Tajul Ariffin, Ahmad Mubarak; Hassan, Mohd Fahrul; Yunos, Muhamad Zaini (Penerbit UTHM, 2018)
In tnis study, Polycaprolactone/Polylactide (PCL/PLA) was plasticized by Polyethylene Glycols (PEGs) with three different molecular weights (Mw=400, 6000 and 10,000g/mol) with the objective to determine the effect of different molecular weight and percentage of PEG on the mechanical properties of PCL/PLA/PEG composites. The effects of content and molecular weight of PEG on the mechanical properties of PCL/PLA/PEG were studied by tensile and impact tests. The tensile test were carried out using Instron 5567 Universal Testing Machine meanwhile the impact test were carried out using Charpy Impact Testing Machine. The results revealed that, increasing in molecular weight of PEG could significantly improve the tensile and impact strenght of PCL/PLA. The results also shows that with increasing molecular weight of PEG, the tensile strength and modulus of elasticity of PCL/PLA/PEG composite were also increased. However, with the increasing of PEG content from 5phr to 15phr on PCL/PLA/PEG composites, it decreases the tensile strength and Young's modulus. Meanwhile from the Charpy impact test, it shows that the impact strength of PCL/PLA/PEG composites increased as the molecular weight of PEG increased from 400 to 10,000. The overall results demonstrated better mechanical properties of PCL/PLA/PEG composites can be achieved by optimizing the content and molecular weight of PEG. The introduction of PEG molecular weight increased the intermolecular force and enhanced the mobility of PCL/PLA chains, thus improving mechanical properties of PCL/PLA.